2017
DOI: 10.5860/lrts.61n2.93
|View full text |Cite
|
Sign up to set email alerts
|

Can RDA Content, Media, and Carrier Coding Improve Discovery Facet Mapping?

Abstract: T he online public catalog interface of the Z. Smith Reynolds Library at Wake Forest University (WFU) has provided users with the option of faceted searching since 2009. Although faceting is undoubtedly useful to the discovery process, we found that our system's default facet mapping was inadequate for our researchers' needs, particularly regarding the faceting of bibliographic formats, and our librarians have worked extensively to revise this mapping. These revisions have relied on creating complex decision t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Dodatkowe problemy sprawia wielość synonimów na oznaczenie tych grup, takich, jak kategoria, atrybut, klasa, pojęcie lub filtr (La Barre, 2012, p. 96). W efekcie wybór faset do stosowania w OPAC bardziej zależy od stosowanego formatu rekordu bibliograficznego (zazwyczaj MARC) niż tradycyjnej analizy fasetowej (Sokvitne, 2006;McCallum et al, 2017), pomimo krytyki takiego postępowania (Broughton & Slavic, 2007, p. 731). Jak pisze Le Barre (2007) projektanci i implementatorzy systemów fasetowych w swojej pracy nie przejmują się zbytnio zasadami tradycyjnej analizy i klasyfikacji fasetowej.…”
Section: Ewolucja Opac Jako Gatunku Tekstuunclassified
“…Dodatkowe problemy sprawia wielość synonimów na oznaczenie tych grup, takich, jak kategoria, atrybut, klasa, pojęcie lub filtr (La Barre, 2012, p. 96). W efekcie wybór faset do stosowania w OPAC bardziej zależy od stosowanego formatu rekordu bibliograficznego (zazwyczaj MARC) niż tradycyjnej analizy fasetowej (Sokvitne, 2006;McCallum et al, 2017), pomimo krytyki takiego postępowania (Broughton & Slavic, 2007, p. 731). Jak pisze Le Barre (2007) projektanci i implementatorzy systemów fasetowych w swojej pracy nie przejmują się zbytnio zasadami tradycyjnej analizy i klasyfikacji fasetowej.…”
Section: Ewolucja Opac Jako Gatunku Tekstuunclassified
“…Although they judged the CMCs to be more granular and specific than GMDs, they found that "CMCs alone do not provide for sufficiently robust faceting of public catalog searches," primarily because of their ILS's limitations and the MARC format. 44 Other libraries addressed the issue by hybridizing catalog records, with some adding GMDs to their RDA records and many others retrospectively adding the 33X fields to their AACR2 records. 45 Mississippi State University's catalogers took this approach one step further, concluding that retaining GMDs was the best way to support user tasks, but also determined that an even more effective solution was to update legacy GMD terms with more item-specific terms.…”
Section: Gmd Questionsmentioning
confidence: 99%